2016
DOI: 10.4269/ajtmh.15-0585
|View full text |Cite
|
Sign up to set email alerts
|

Independent Evaluation of the Rapid Scale-Up Program to Reduce Under-Five Mortality in Burkina Faso

Abstract: We conducted a prospective evaluation of the “Rapid Scale-Up” (RSU) program in Burkina Faso, focusing on the integrated community case management (iCCM) component of the program. We used a quasi-experimental design in which nine RSU districts were compared with seven districts without the program. The evaluation included documentation of program implementation, assessments of implementation and quality of care, baseline and endline coverage surveys, and estimation of mortality changes using the Lives Saved Too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 12 publications
1
51
1
Order By: Relevance
“…Consistent with existing studies, the evaluation method for this study is difference‐in‐differences (DD). Based on mixed‐effects negative binomial modeling , the preferred specification is given by: Yijt=β0+β1INTij+β2POSTt+β3INTijPOSTt+Xijtγ1+LGAjγ2+α1TRENDt+MTHtα2+α3PEAKt+uij+εijt…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…Consistent with existing studies, the evaluation method for this study is difference‐in‐differences (DD). Based on mixed‐effects negative binomial modeling , the preferred specification is given by: Yijt=β0+β1INTij+β2POSTt+β3INTijPOSTt+Xijtγ1+LGAjγ2+α1TRENDt+MTHtα2+α3PEAKt+uij+εijt…”
Section: Methodsmentioning
confidence: 88%
“…The assumption does not hold in dynamic settings. Empirical evidence has indicated that, if implemented properly for a sufficiently long period, antimalarial interventions can interrupt malaria transmission, reducing the incidence rate and, consequently, the number of malaria‐related facility visits over time . The introduction of free RDTs, in particular, has been associated with a lower rate of clinical services utilization, with non‐malaria cases being more effectively screened out .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…iCCM has been shown in smaller experiments to improve child health and reduce child mortality [5]. However, recent evaluations of nationally scaled-up versions have been mixed [6, 7]. …”
Section: Introductionmentioning
confidence: 99%